The Association of Intraventricular Hemorrhage and Acute Kidney Injury in Premature Infants from the Assessment of the Worldwide Acute Kidney Injury Epidemiology in Neonates (AWAKEN) Study - Stoops, Christine; Boohaker, Louis; Sims, Brian; Griffin, Russell; Selewski, David T; Askenazi, David (Neonatology (Basel, Switzerland), 2019)
Acute kidney injury (AKI) and intraventricular hemorrhage (IVH) are common in premature infants. We previously demonstrated that infants with AKI have a higher hazards ratio to develop grade ≥2 IVH when controlling for confounders. However, that single-center study was unable to show an overall association. To test the hypothesis that infants diagnosed with AKI have an increased risk of IVH independent of variables associated with both AKI and IVH, we performed a study on 825 infants from the Assessment of Worldwide Acute Kidney Injury Epidemiology in Neonates (AWAKEN) study (a 24-center multinational retrospective cohort). A neonatal modified KDIGO definition of AKI was used based on serum creatinine (SCr) and/or urine output criteria. Baseline SCr was defined as the lowest previous value. IVH was diagnosed with head ultrasounds. AKI was documented in 22.2% (183/825) of infants and IVH in 14.3% (118/825). Infants with AKI (n = 183) were more likely to have IVH (26.8%, 49/183) than those without AKI (n= 642) who had IVH (10.7%, 69/642, p < 0.0001). After controlling for 5-min Apgar score, vasopressor support within the first week of age, and gestational age, infants with AKI had 1.6 times higher adjusted odds to develop any grade IVH (95% CI 1.04-2.56). Furthermore, infants of gestational age of 22-28 weeks had 1.9 times higher adjusted odds to develop IVH (OR 1.87, 95% CI 1.08-3.23). We present the first multicenter evaluation of the association between AKI and IVH in premature infants showing a significant independent association between AKI and IVH. Development of strategies to reduce AKI may also reduce IVH.